2021
DOI: 10.1155/2021/9920234
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis Reveals Central Role for Tumor-Infiltrating Immune Cells in Uveal Melanoma Progression

Abstract: Tumor-infiltrating immune cells are capable of effective cancer surveillance, and their abundance is linked to better prognosis in numerous tumor types. However, in uveal melanoma (UM), extensive immune infiltrate is associated with poor survival. This study aims to decipher the role of different tumor-infiltrating cell subsets in UM in order to identify potential targets for future immunotherapeutic treatment. We have chosen the TCGA-UVM cohort as a training dataset and GSE22138 as a testing dataset by mining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 111 publications
(173 reference statements)
1
8
0
Order By: Relevance
“…Other evidence reinforced the relationship between immune cell infiltration and prognosis, with the exception of some genetically distinct subgroups [ 28 ]. Recently, a bioinformatic analysis and CD8+ gene signature confirmed the prognostic role of CD8 in UM [ 17 , 18 ]. In addition, a recent study performing single cell analyses of the tumor and the microenvironment in primary and metastatic UMs outlined genomic complexity, as well as revealing a different subset of CD8+ T cells expressing checkpoint marker LAG3 but not PD1 or CTLA4 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other evidence reinforced the relationship between immune cell infiltration and prognosis, with the exception of some genetically distinct subgroups [ 28 ]. Recently, a bioinformatic analysis and CD8+ gene signature confirmed the prognostic role of CD8 in UM [ 17 , 18 ]. In addition, a recent study performing single cell analyses of the tumor and the microenvironment in primary and metastatic UMs outlined genomic complexity, as well as revealing a different subset of CD8+ T cells expressing checkpoint marker LAG3 but not PD1 or CTLA4 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that the high immunosuppressive tumor microenvironment (TME) present in UMs caused a failure in the activation of CD8+ cells, which could not express their strong antitumoral function [ 17 ]. Unfortunately, in this context, the host’s immune system could inadvertently promote tumor growth [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the lasso method is stricter than ridge regression due to its diamond-shaped constraint region instead of the elliptical constraint region of ridge regression, which does not set the coefficients to zero [40]. An alternative for ridge regression in the app involves the BeSS algorithm that has been recently used in the literature [41]. The "CPH" main tab in the app extracts the best subsets of input genes directly from the CPH model, and the results can be compared with those from the "glmnet" and "BeSS" tabs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a high metastatic infiltration of CD8+ T cells and macrophages (CD68+) correlated with longer overall survival for patients undergoing isolated hepatic perfusion as treatment of liver metastases [ 109 , 110 ]. Yet most transcriptomic and bioinformatic approaches have shown a correlation between TILs and short survival [ 111 ]. A different scenario appeared when studying the functional properties of T-cells and macrophages in depth and measuring tumor-immune cell distances in liver and extra liver metastases.…”
Section: Pathophysiology Of Um Metastasismentioning
confidence: 99%